The Contribution of Family Edification, Mutualism, and Kinships Against The Tolerance Values in Tana Toraja - Hadi Pajarianto; Junaidi Junaidi (Karsa: Journal of Social and Islamic Culture, 2020)
Indonesia is a multicultural country. It consists of many different races, religion, and ethnicities.  That is why the tolerance attitude is important to minimize the intolerance cases which seem to raise lately. Tolerance is an attitude to let anyone to be different and to appreciate the diversity as recognition of human right. Teachers play a strategic role in implementing values of tolerance, by placing diversity within the frame of brotherhood and humanity based. This study uses an ex-post-facto approach. The research instruments used are questionnaires that meet the validity and reliability. It is analyzed using the Pearson correlation test. The finding of this study shows that family edification, mutualism, and kinship have strong correlation with the tolerance attitude of the early childhood teachers in Tana Toraja. Kinship gives the highest contribution to the tolerance attitude of the early childhood teachers in Tana Toraja.  It is in line with the characteristic of Toraja’s community who appreciate kinship above all the existing diversities, including the diversity in religion and belief. The kinship in Toraja’s community is bound by Tongkonan which philosophically has a strong sense of brotherhood among extended families (clans), and keeps all the existing diversities aside